Structure and Characteristics of Plant-Frugivore Network in an Urban Park: A Case Study in Nanjing Botanical Garden Mem. Sun Yat-Sen - Manyu Zhang; Caihong Lu; Qian Han; Changhu Lu (Diversity, 2022)
Interaction between animals and plants is an important way to maintain terrestrial biodiversity and ecosystem function, but little is known about the structure of reciprocal networks between fruit plants and frugivore birds in urban habitats. To explore the characteristics of the plant–frugivore network and network roles of species, we observed the fruit ripening phenology of 21 species of fruit plants and the interactions between these plants and 39 species of frugivore birds during the whole year in a large urban park. Then, we assessed the characteristics of the total plant–frugivore and seasonal networks, and analyzed the network roles of species and the relationship between their network roles and ecological traits. Fruit ripened mainly in autumn and winter, and interaction connections in the two seasons contributed 39.68% and 44.83% to the total network, respectively. The specialization (H2′), connectance (C), nestedness, and interaction evenness (<semantics>eH2</semantics>) of the network were lower in autumn and winter, while the interaction diversity was higher. Compared with the networks (N = 1000) generated by the null model, the observed network exhibited higher nestedness and interaction diversity (E2) and lower specialization (H2′), connectance (C), and interaction evenness (<semantics>eH2</semantics>). A correlation analysis combining ecological traits and network roles showed that plants with black fruit had higher effective partners and partner diversity, while other traits of plants and birds were not significantly correlated with their network parameters. The important plants (N = 6) and birds (N = 3) contributed to 71.78% and 67.55% of the total network connection, they were mainly evergreen plants with black and red drupes and omnivorous generalist birds with medium and large sizes. Our research highlighted the seasonal differences in urban plant–frugivore network and the value of important species in maintaining network structures and providing ecosystem services.